Usunięcie policjanta ze szkolenia zawodowego podstawowego z uwagi na popełnienie przez niego czynu o znamionach wykroczenia albo przewinienia dyscyplinarnego, jeżeli popełnienie czynu jest oczywiste i uniemożliwia jego udział w szkoleniu: [Removal of the police officer from vocational basic training course due to committing by him deed displaying the characteristics specified under offence or disciplinary offence if commitment this deed is obvious and makes it impossible for the police officer to remain in vocational basic training course] (Studia Prawnicze / The Legal Studies, 2022)
Artykuł został w całości poświęcony problematyce usunięcia policjanta ze szkolenia zawodowego podstawowego na podstawie § 43 ust. 3 pkt 1 rozporządzenia Ministra Spraw Wewnętrznych i Administracji z dnia 19 czerwca 2007 r. w sprawie szczegółowych warunków odbywania szkoleń zawodowych oraz doskonalenia zawodowego w Policji. Skoncentrowano uwagę na przesłance warunkującej zastosowanie tej instytucji oraz omówiono poszczególne jej elementy. Wskazano również na konieczność rozwiązania stosunku służbowego z policjantem usuniętym ze szkolenia zawodowego podstawowego. Usunięcie funkcjonariusza ze szkolenia zawodowego podstawowego uniemożliwia ponowne skierowanie go na to szkolenie. Z kolei dalsze zatrudnienie policjanta, który nie posiada kwalifikacji zawodowych podstawowych, a zatem niezdolnego do efektywnego pełnienia służby, w sposób oczywisty narusza ważny interes służby i determinuje zwolnienie go na podstawie art. 41 ust. 2 pkt 5 ustawy o Policji. This paper is entirely devoted to the issue of removal the police officer from vocational basic training course based on the paragraph 43 (3) (1) Regulation of the Minister of Internal Affairs and Administration of 19 June 2007 on the detailed conditions of vocational training and professional development in the Police. Attention was focused on premises which determine the application of this legal institution and discussed of its elements individually. There were also indicated the necessity to resolve service relationship with the police officer who was removed from vocational basic training course. Removal the police officer from vocational basic training course prevents re-referral his or her on this training course. On the other hand, the further employment the police officer who does not have vocational basic qualifications, and therefore is unable to perform the service effectively, obviously violates the important service interest and determines to dismiss him or her based on Art. 41 (2) (5) Act on the Police.